TEACHERS’ FEEDBACK ON ENGLISH SYLLABUS WITH LOCAL VALUES FOR ELEMENTARY STUDENTS - Puspitasari, Ika Puspitasari; Ratri, Devinta Puspita; Tyas, Peptia Asrining (LLT Journal: A Journal on Language and Language Teaching, 2021)
The elimination of English subject for elementary school in curriculum of 2013  which has been regulated under the Government of the Republic of Indonesia’s Regulation number 32 year 2013 about the alteration of Government Regulation number 19 year 2005 about National Standard of Education affects on the absence of syllabus as guideline for teaching and learning process. Therefore, on previous study, a set of English syllabus for elementary school was developed to provide English teachers with guideline in teaching. To provide students with closer exposure on local character building, the syllabus was developed based on local value. In the process of syllabus development, try out was done to get feedback on its implementation on the syllabus in the teaching process. Moreover, feedback from teachers’ forum toward the syllabus was also obtained. The feedback received becomes a valuable input toward the improvement of the English syllabus.